Social definition in child-care in the Irish republic - models of the child and child-care intervention - O'Sullivan, Denis (Economic & Social Studies, 1979)
This paper developed from a case study of an Irish child-care institution and considers some fundamental definitions in child care in the Irish Republic. Three main aspects are explored: the transition from a social risk to a deprived model of the child under the influence of an emergent child-care movement; the evolution of a developmental model of child-care intervention in official reports of the 'sixties and 'seventies, in contrast to the segregation and training model obtaining since the inception of the Industrial School System, and the role of definitions of the child in care in boundary maintenance mechanisms. This paper argues for the analysis of the cognitive and evaluative bases of child-care thought and recommends a number of topics for socio-historical, conceptual and empirical research.
Keywords: Child care - Ireland; Industrial schools - Ireland